CONDUTA ANESTESIOLOGIA EM PACIENTES SICLEMICOS - Vianna, P. T.G.; Machado, P. E.A.; Braz, J. R.C. (My University, 1975)
The importance of sickle cell anemia or falciform anemia for anesthesiology is reviewed Special attention is given to heterozigotus asymptomatic sickle cell anemia patients, who develop an acute falcization crisis started by hypoxemia, produced by the anesthetic surgical trauma. The principles of conduct are based on the pre operatory diagnosis. All Black patients and their families are submitted to the falcization test and when it is positive, the complementary diagnosis is done with hemoglobin electrophoresis. Rigorous precautions are taken for the sickle cell anemia patients in order to avoid hypoxemia, hypotension and circulatory delay; besides, chloroquine diphosfate is prophylactically used in pre, inter and post operatory procedures.
An anesthesiologic approach to the sickle cell disease patient